Open-angle glaucoma in diabetic patients’ prevalence and risk factors: a cross-sectional study in Sudan - Salih, Omyma Abbas Banaga; Hamed, Ehab (International Journal of Research in Medical Sciences, 2020)
Background: Diabetic patients are at increased risk of glaucoma compared to the general population. Risk factors for glaucoma that is specific to diabetic patients include increased IOP, retinopathy and neovascular changes and years since diagnosis of diabetes. This cross-sectional study aims to report on the prevalence of glaucoma in diabetic patients in community diabetes centre in Sudan and examine associations with previously reported risk factors. Methods: A cross-sectional study was carried out in Omdurman specialised diabetic healthcare centre in Sudan. A total of 300 patients consented to participation. All patients filled in a survey for both demographics and diabetic disease history then had an assessment for glaucoma by an ophthalmologist. The assessment included examination of the anterior segment, optic nerve assessment and fundus examination using a stereoscopic slit lamp, intraocular pressure (IOP) measurement using tonometry, peripheral anterior chamber configuration and depth assessments using gonioscopy and central visual field assessment using perimetry. Results: Prevalence of open-angle glaucoma diagnosis was 2.8% among diabetic patients who were included in this study. Family history for glaucoma was significantly associated with increased risk of open-angle glaucoma (OR 5.67, 95% CI 1.74-18.45). Retinopathy was also associated with an increased risk of developing the condition (OR 3.1, 95% CI 1.11-8.51). Gender, years since diabetes diagnosis and medications did not have significant associations. Conclusions: Patients with diabetes are at increased risk of developing open-angle glaucoma, but the prevalence among the diabetic population attending community diabetes centre in Sudan remains low. Among different clinical determinants, diabetic retinopathy and genetic determinants may explain the increased risk in the diabetic population.